Sustaining economic growth in sub-Saharan Africa: Do FDI inflows and external debt count? - Udi Joshua; David Babatunde; Samuel Asumadu Sarkodie (Journal of Risk and Financial Management, 2021)
The quest for the attainment of economic development is sought after by all global economies, which by effect is expected to transcend to improving livelihoods and standard of living. However, several factors hinder the process of achieving sustained economic development, especially in developing countries. In this regard, assessing the extent of economic expansion orchestrated by foreign direct investment (FDI) inflows in vulnerable economies such as Sub-Saharan Africa (SSA), particularly in the face of the significant fall in global FDI inflow, is worthwhile. In essence, this study ascertains the impact of FDI inflows and external debt on economic growth amidst decline in FDI inflows and excessive foreign borrowings. The mixed order of integration from the stationarity test underpins the adoption of autoregressive distributed lag (ARDL) approach for data covering the period 1990 to 2018. The empirical results found FDI inflows play a crucial role in achieving economic expansion in the region. On average, FDI inflows, external debt, and foreign aids are more useful in expanding the economy compared to trade openness and exchange rate. Thus, this study recommends the need for SSA to open its economic borders for external capital, viz. FDI. A peaceful economic and political environment is a pre-condition to attract and maintain potential foreign investors. Stability in exchange rates is critical in achieving growth in FDI and other foreign resources. However, caution is required, especially in administration of external resources. Particularly, contracting external debt must strictly be driven by economic reasons rather than political motivation. Borrowed funds could be injected mainly into productive streams with the highest investment returns to boost economic development.
Keywords: F15; F43; F3; O14; 330; economic growth; foreign direct investment; Sub-Saharan Africa; sustainable development